(untitled) - Karmen, Andrew (Belmont, CA, 2007)
The book is a innovative and comprehensive guide that offers balanced coverage on this controversial subject. A must-have for anyone interested in this field!
Keywords: Victims of crimes,Nạn nhân của tội phạm; United States,Mỹ